Risk factors of sentinel lymph node metastasis in early-stage invasive breast cancer - Tong Wang; Yilin Wang; Yilin Xu; Qi Cui (Scientific Reports)
Abstract This study aimed to determine the key risk factors affecting sentinel lymph node (SLN) metastasis and to help improve the selection of appropriate candidates for SLN biopsy (SLNB). A total of 2143 cases that underwent SLNB were included. Multivariate analysis included the statistically significant parameters in univariate analysis and revealed the independent risk factors for SLN metastasis: age younger than 40 years old, central tumor location, tumor larger than 3 cm, round-shaped and cortex-thickened axillary lymph node examined by ultrasound, lymphovascular invasion (LVI), and histological classification of invasive breast carcinoma of no special type (IBC-NST) and invasive micropapillary carcinoma (IMPC). The most powerful prognostic factor for SLN metastasis is IMPC (P < 0.001), which increases more than 11 times the risk of SLN positivity. The distance between the tumor and nipple of ≤ 1 cm, LVI, and age younger than 40 years old are also with P value < 0.001. The identification of predictors for SLN metastases based on clinicopathological characteristics could guide the SLNB practice conveniently, especially in less developed areas. Patients with theses revealed adverse features should undergo SLNB with deliberation to avoid a second surgery, particularly when multiple risk factors exist.